2015
DOI: 10.1371/journal.pone.0139998
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Death among AIDS Patients after Introduction of Free Combination Antiretroviral Therapy (cART) in Three Chinese Provinces, 2010–2011

Abstract: IntroductionAlthough AIDS-related deaths have had significant economic and social impact following an increased disease burden internationally, few studies have evaluated the cause of AIDS-related deaths among patients with AIDS on combination anti-retroviral therapy (cART) in China. This study examines the causes of death among AIDS-patients in China and uses a methodology to increase data accuracy compared to the previous studies on AIDS-related mortality in China, that have taken the reported cause of death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Second, we did not analyze the impact of late ART initiation on the outcome of HIV-positive patients because of the unavailability of follow-up data. However, many other studies [ 1 , 8 , 9 ] have demonstrated that the late initiation of ART significantly weakens its effect. Thirdly, those patients with missing CD4 cell count were excluded out of this study and it might result in selection bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we did not analyze the impact of late ART initiation on the outcome of HIV-positive patients because of the unavailability of follow-up data. However, many other studies [ 1 , 8 , 9 ] have demonstrated that the late initiation of ART significantly weakens its effect. Thirdly, those patients with missing CD4 cell count were excluded out of this study and it might result in selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…What even worse is that many HIV-positive people receive late HIV diagnoses [57]. Both of these factors weaken the effect of ART among HIV-positive populations [8, 9]. Therefore, the vital steps to maximize the efficacy of ART for HIV infected patients would be expanding screening of HIV antibody and initiating ART as soon as possible when the patients meet the criteria [10].…”
Section: Introductionmentioning
confidence: 99%
“…All HIV-1-infected subjects were examined by medical screening, and voluntarily received cART. The treatment regimen and algorithm TDF+3TC+EFV (17 patients) or AZT+3TC+NVP (1 patient) were carried out according to the China free cART manual [ 29 ], in which the threshold for cART eligibility was recommend as CD4+ T cells < 350/μL [ 30 ] and suggested therapy regimen was AZT/d4T+3TC+NVP/EFV.…”
Section: Methodsmentioning
confidence: 99%
“…For reasons that remain poorly defined, long-term treated HIV-infected persons have an expected life span that is substantially shorter than that of their HIV-uninfected peers 7–10 . This shortened life span is largely due to an increased risk of some “non-AIDS” complications, encompassing heart disease, cancer, liver disease, kidney disease, bone disease, and neurocognitive decline 8 many of which complications are similar to that observed generally among the elderly. In addition, the fact of these diseases are degenerative in nature will affect the quality of life and functionality.…”
Section: Introductionmentioning
confidence: 97%
“…Despite the unquestioned success, combination antiretroviral therapy does not fully restore health. For reasons that remain poorly defined, long-term treated HIV-infected persons have an expected life span that is substantially shorter than that of their HIV-uninfected peers [7][8][9][10] . This shortened life span is largely due to an increased risk of some "non-AIDS" complications, encompassing heart disease, cancer, liver disease, kidney disease, bone disease, and neurocognitive decline 8 many of which complications are similar to that observed generally among the elderly.…”
Section: Introductionmentioning
confidence: 99%